FORMATION OF OLYMPIC KNOWLEDGE IN CHILDREN AND ADOLESCENTS AND ESSENCE OF OLYMPIC EDUCATION - Kosse Rulen Bekirovich (Galaxy International Interdisciplinary Research Journal, 2023)
In this article improvement of physical education and sports, training of teachers, relevance and necessity of Olympiad education, local and foreign of experts practical experiences general business issues were discussed.